The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/adem.201900698
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Warm and Combined Warm and Low‐Temperature Processing Routes for the Equal‐Channel Angular Pressing of Pure Titanium

Abstract: Two different processing routes are used to investigate the microstructure and strength of commercial purity (CP) titanium of grade 4 processed by equal‐channel angular pressing (ECAP). In the combined temperature (CT) route, the specimens are pressed at 723 K in the first pass and at 373 K in the second pass, but in the warm temperature (WT) route, the specimens are pressed through two passes at 723 K. Both routes lead to an inhomogeneous microstructure with an average grain size of ≈1.5 and ≈1.7 μm after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(55 reference statements)
0
3
0
1
Order By: Relevance
“…It can be seen that the temperature has a certain influence on the ECAP processing technology. Bulutsuz et al obtained the average grain size of pure Ti after two passes of the composite temperature, which were 1.5 μm and 1.7 μm, respectively [76]. A al.…”
Section: Grain Size From 01-1 μMmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the temperature has a certain influence on the ECAP processing technology. Bulutsuz et al obtained the average grain size of pure Ti after two passes of the composite temperature, which were 1.5 μm and 1.7 μm, respectively [76]. A al.…”
Section: Grain Size From 01-1 μMmentioning
confidence: 99%
“…The same conclusion was found in pure Ti[74] and pure Al[75]. Figure11shows the microstructures under different route treatments.Bulutsuz et al obtained the average grain size of pure Ti after two passes of ECAP at the composite temperature, which were 1.5 µm and 1.7 µm, respectively[76]. Attarilar et al found that the average grain size of pure Ti reached 1.09 µm after four passes of ECAP at 400 • C [77], Ebrahimi and Attarilar measured an average grain size below 0.5 µm after four passes of ECAP at 450 • C[78].…”
mentioning
confidence: 99%
“…[19,20] Multistage SPD is used to obtain ultrafine-grained (UFG) or even nanostructured Ti products. Equal channel angular pressing (ECAP), [21] high-pressure torsion (HPT), [22,23] and hydrostatic extrusion (HE) [24,25] are commonly used methods to refine grains in CP-Ti. Recent years have seen great progress in those deformation techniques as well as in the characterization of UFG/nano Ti products, especially for biomedical applications (Figure 1).…”
Section: Grain Refinement To the Nanoscale-an Alternative To Ti6al4vmentioning
confidence: 99%
“…Malzemelere uygulanan Aşırı Plastik Deformasyon (APD) sonrasında yapıda artan gerinim miktarı ile yapıdaki iri tanecik boyutu ultra ince taneye hatta nano yapıya dönüşmektedir. Yüksek Basınç Altıda Burma (YBAB), Eş Kanal Açılı Presleme (EKAP) literatürde kullanılan APD tekniklerinden bir kısmıdır [8][9][10][11]. APD teknikleri tane yapısını inceltirken malzeme özelliklerini iyileştirmektedir.…”
Section: Introductionunclassified